Pengaruh Penambahan Hidroksi Apatit Dari Serbuk Cangkang Telur Terhadap Kekuatan Tekan Semen Ionomer Kaca Modifikasi Resin (SIKMR) - Kisman, Andi Musdalifa, drg. Noor Hafida Widyastuti, Sp.KG (2017)
Resin modified glass ionomer cements are restorative material produced from nature of the conventional glass ionomer cements with composite resin which aims to improve the mechanical properties, reduced sensitivity to water, as well as reducing the solubility properties owned by the conventional glass ionomer cement. Resin modified glass ionomer cements has several advantages that can attach emails without etching, removing flour, resistant to moisture and the failure rate of attachment is small. The purpose of this study is to notice at the effect of adding hydroxy apatite from eggshell powder to the material compressive strength of resin modified glass ionomer cements. This study used sample divided into 2 groups resin modified glass ionomer cements with addition of hydroxy apatite and the second group is resin modified glass ionomer cements without addition of hydroxy apatite. The sample size is 3 mm of diameter and 6 mm height with 32 pieces which 16 pieces in each group. Samples were soaked in distilled water for 24 hours and incubated at a temperature of 370 C. The compressive strength testing was using universal testing machine with speed of5 mm/min. The test data were analyzed using t-test Independent test. The results showed that between the two study groups there are significantly value differences in compressive strength, with p = 0.000 (P <0.05) that it can be concluded that there are differences in the compressive strength of resin modified glass ionomer cement with the addition of hydroxy apatite and without addition of hydroxy apatite. The compressive strength of resin modified glass ionomer cement with the addition of the results of the hydroxy apatite result greater in compressive strength than without the addition of hydroxy apatite.